2003
DOI: 10.1111/j.1559-1816.2003.tb01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Risky and Precautionary Sexual Behaviors Among Single and Married White Women1

Abstract: Risky and precautionary sexual behaviors were examined in a community sample of 260 single and married/cohabitating White women. Structural equation modeling was used to assess the ability of age, socioeconomic status (SES), marital status, religiosity, and 9 health belief constructs to predict risky sexual behavior with one's partner, using a barrier method of birth control, unintended pregnancies, and number of sexual partners in the past year. The pattern of results suggests that single White women appear t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 54 publications
0
11
1
1
Order By: Relevance
“…Religious involvement has been found to be associated with abstinence [12,14], delay in sexual debut and lower rates of intercourse [13,27]. In adult female community samples, religious involvement was not predictive of contraceptive decision making [22] or risky sexual behaviors [23]. This is not consistent with the current findings for attendance.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Religious involvement has been found to be associated with abstinence [12,14], delay in sexual debut and lower rates of intercourse [13,27]. In adult female community samples, religious involvement was not predictive of contraceptive decision making [22] or risky sexual behaviors [23]. This is not consistent with the current findings for attendance.…”
Section: Discussioncontrasting
confidence: 50%
“…It was concluded that religious involvement may serve as a protective factor due to reduced sexual risk taking. However, two other studies found that religious involvement was not a significant predictor of contraceptive decision-making [22] and risky sexual behaviors [23] in adult female community samples. In summary, although not all studies are consistent with a protective role of religiosity, the majority of studies suggest that religious involvement is negatively associated with sex-related HIV risk behaviors.…”
Section: Studies Of Non-college Adultsmentioning
confidence: 99%
“…For example, demographic variables such as gender, age, educational attainment, race, and marital status have been associated with HIV risk (Klein, Elifson, Sterk, & Theall, 2002;Newcomb et al, 1998;Smereck & Hockman, 1998;Wayment et al, 2003). In addition, childhood maltreatment, including physical, sexual, and emotional abuse and neglect, has been linked to HIV risk in adulthood (Bensley, Eenwyk, & Simmons, 2000;Morrill, Kasten, Urato, & Larson, 2001).…”
mentioning
confidence: 97%
“…Heavy episodic drinking also is associated with a broad range of risk behaviors, including tobacco use and risky sexual activity, such as unprotected sex and multiple sex partners (Hutton et al, 2008). Younger, single women may be more vulnerable as they are more likely to engage in risky sexual behavior than their married counterparts (Wayment et al, 2003). …”
Section: Discussionmentioning
confidence: 99%